ANALISIS KEPUASAN MAHASISWA TERHADAP PELAYANAN ADMINISTRASI AKADEMIK DAN KEMAHASISWAAN - Sri Sundari; Arinastuti (Majalah Imiah Manajemen & Bisnis, 2021)
Student satisfaction as a user of educational services in tertiary institutions is very important for the progress of an educational institution. Student satisfaction contributes to the success of a college because student satisfaction will have an impact on its loyalty to the institution. Loyal students will be a very valuable asset for the university, because students will be willing to promote their institutions to others, provide positive feedback on institutions, reduce the influence of attacks from competitors from the same institution and enhance the positive image of the institution. One factor in achieving user satisfaction in a service business is service quality. With a quality service that is expected to increase user satisfaction. Therefore this research was conducted as an effort to evaluate employee performance in serving students in the academic and student administration. Attributes studied include reliability, responsiveness, assurance, empathy and tangibles. In addition, to analyze which attributes are considered most important by students. The analytical method used is "Multiatribute Attitude Model" (MAM). From the test results it can be concluded that students are satisfied with the service received as evidenced by the responses given to the services received are included in the criteria for a good interval scale value. Based on the order of importance according to students' assessments the responsiveness attribute is the most important attribute, the next order is reliability, assurance, emphaty and tangibles. Keywords: Service Quality, reliability, responsiveness, assurance, empathy and tangibles.